Poverty Alleviation Based On Economic Literacy And Social Capital In Improving Economic Welfare In Coastal Communities North Minahasa Regency, North Sulawesi Provence, Indonesia - Tamboto, Henry J.D; Manongko, Allen A.Ch.; Manengkey, James J. (International Journal of Scientific Research and Management (IJSRM), 2018)
The research problem is related to the economic welfare of coastal communities who are fishermen. The fundamental thing of this research is that poverty from the fishermen's household community is thought to be caused by inability to manage income and lack of horizontal relations between fellow communities. So that underlies various research findings, providing space for the concept of economic literacy and social capital can explain its influence on the economic welfare of the community. This research generally attempts to produce new methods and theories and policies in addressing the problems of coastal communities.This study aims to: 1). Analyzing and explaining partially the influence of economic literacy and social capital on the economic welfare of coastal communities; and 2). Analyze and explain simultaneously the influence of economic literacy and social capital on the economic welfare of coastal communities. The population in this study were all coastal communities (fishing communities) in North Minahasa Regency,North Sulawesi province,Indonesia. Number of samples from the calculation through the formula of Daniel and Terrel obtained 100 respondents. Sampling using purposive sampling technique. And data analysis using multiple regression, with SPSS application. The findings of this study indicate that: 1). economic literacy has a significant effect on economic prosperity; 2). social capital has a significant effect on economic welfare; 3). economic literacy and social capital have a significant effect on economic prosperity